A clinical study of intestinal stomas in emergency laparotomy: its complications - Krishnaswamy, Jawahar; Kumar, Senthil; K., Mukesh; Rahman, Khalilur (International Surgery Journal, 2017)
Background: Intestinal stoma is an opening for fecal diversion. The purpose of the present study was to identify indications for emergency laparotomy, commonly performed intestinal stomas and to study complications related to it. Methods: This is a prospective study was carried out in a surgical unit of Saveetha Medical College & Hospital, Chennai, Tamilnadu, from August 2012 to August 2013. Data was collected by meticulous history taking including age, gender, indication, type of stoma, type of surgery, careful clinical examination, appropriate operative findings and follow up of the cases. The results were collected, analyzed and compared. Results: A total of 74 patients were evaluated age ranged between 16 to 78 years. Male to female ratio was 7:2. The most common type of stoma made was loop ileostomy (60%) followed by end ileostomy (30%) and loop colostomy (9%). Main indication for emergency laparotomy was intestinal obstruction (44%). The most common type of stoma performed was loop ileostomy (60%). The most dreaded complication of stomal closure is anastomotic leakage. Conclusions: Early referral to the tertiary hospital, early diagnosis, proper preoperative management like intravenous fluids, antibiotics, etc., early detection and prevention of hypotension, reduction of time duration for emergency laparotomy, close post-operative monitoring definitely reduce the morbidity and mortality of stomal closure, when intestinal stomas kept for emergency cases.